Avian host composition, local speciation and dispersal drive the regional assembly of avian malaria parasites in South American birds. Issue 10 (25th May 2019) - Fecchio, Alan; Bell, Jeffrey A.; Pinheiro, Rafael B.P.; Cueto, Victor R.; Gorosito, Cristian A.; Lutz, Holly L.; Gaiotti, Milene G.; Paiva, Luciana V.; França, Leonardo F.; Toledo‐Lima, Guilherme; Tolentino, Mariana; Pinho, João B.; et al.
Abstract: Identifying the ecological factors that shape parasite distributions remains a central goal in disease ecology. These factors include dispersal capability, environmental filters and geographic distance. Using 520 haemosporidian parasite genetic lineages recovered from 7, 534 birds sampled across tropical and temperate South America, we tested (a) the latitudinal diversity gradient hypothesis and (b) the distance–decay relationship (decreasing proportion of shared species between communities with increasing geographic distance) for this host–parasite system. We then inferred the biogeographic processes influencing the diversity and distributions of this cosmopolitan group of parasites across South America. We found support for a latitudinal gradient in diversity for avian haemosporidian parasites, potentially mediated through higher avian host diversity towards the equator. Parasite similarity was correlated with climate similarity, geographic distance and host composition. Local diversification in Amazonian lineages followed by dispersal was the most frequent biogeographic events reconstructed for haemosporidian parasites. Combining macroecological patterns and biogeographic processes, our study reveals that haemosporidian parasites are capable of circumventing geographic barriers and dispersing across biomes, although constrained by environmental filtering. The contemporary diversity and distributions of haemosporidian parasites are mainly driven by historical (speciation) and ecological (dispersal) processes, whereas the parasite community assembly is largely governed by host composition and to a lesser extent by environmental conditions.